2020
DOI: 10.15243/jdmlm.2020.073.2201
|View full text |Cite
|
Sign up to set email alerts
|

Copper and arsenic accumulation of Pityrogramma calomelanos, Nephrolepis biserrata, and Cynodon dactylon in Cu- and Au- mine tailings

Abstract: Metallophytes are group of plants that can thrive on metal-rich substrate. These plants have potential in various green technologies. However, it is a must to first identify plants that can absorb heavy metals and tolerate the high concentration in their tissues. This study assessed the ability of plants thriving in a Cu-Au mined areas to uptake copper (Cu), and arsenic (As). The Cu and As content of the dried leaves, root tissues and soils were quantified using Atomic Absorption Spectrophotometer (AAS), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The finding that copper accumulated at higher concentrations in the root than the shoot, is in concordance with several studies (Ancheta et al, 2020;Chua et al, 2019;Claveria et al, 2010;Dahilan and Dalagan, 2017). High root concentrations, or low translocation factors, could indicate phytostabilisation as this process binds the substrate to the plant roots thus reducing mobility of the metal in the soil (Claveria et al, 2010) or the sequestered metal remains solely in the roots, enabling the plant to grow and mature without its health being impacted (Claveria et al, 2010).…”
Section: Metal Partitioning and Phytoextraction/phytomining Potentialsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that copper accumulated at higher concentrations in the root than the shoot, is in concordance with several studies (Ancheta et al, 2020;Chua et al, 2019;Claveria et al, 2010;Dahilan and Dalagan, 2017). High root concentrations, or low translocation factors, could indicate phytostabilisation as this process binds the substrate to the plant roots thus reducing mobility of the metal in the soil (Claveria et al, 2010) or the sequestered metal remains solely in the roots, enabling the plant to grow and mature without its health being impacted (Claveria et al, 2010).…”
Section: Metal Partitioning and Phytoextraction/phytomining Potentialsupporting
confidence: 92%
“…A BF greater than one indicates that a species is a hyperaccumulator, and a BF less than one is indicative of an excluder (Ancheta et al, 2020;Claveria et al, 2020;Novo et al, 2013;Usman et al, 2019;Yashim et al, 2014).…”
Section: Bioaccumulation Factormentioning
confidence: 99%
“…It is known to have a moderate capacity for metal accumulation and antioxidant properties, making it a potential phytoremediation agent for metals in contaminated soils (Manan et al, 2015). This aligns with the report by laporan Ancheta et al (2020) that N. biserrata, along with Cynodon dactylon and Pityrogramma calomelanos, can tolerate heavy metals and are potential candidates for phytostabilization of contaminated soils. Nephrolepis biserrata contains phytochemicals with antioxidant and vermicidal properties, howeverit is not effective as a 4 bactericide (Brice & Yves-Alain, 2021).…”
Section: Introductionsupporting
confidence: 91%
“…Da Silva et al [53] recorded higher Cu bioaccumulation in root parts and high production of C. dactylon biomass -compensates for comparatively low Cu concentration in its tissues by increasing Cu extraction from soil that makes C. dactylon more competent in the phytoremediation process. Ancheta et al [54] observed Cu accumulation of C. dactylon in Cu -mine tailings. They analyzed that higher concentrations of metals accumulated in the root compared to the shoot, validating the current study.…”
Section: Bioconcentration (Bcf %) and Translocation Factor (Tf %) Of ...mentioning
confidence: 99%